A review regarding the 3D facial animation pipeline - de Carvalho Cruz, Artur Tavares; Xavier Natario Teixeira, Joao Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
A large number of 3D facial animation techniques have emerged with different goals, to make the representation of facial expressions more realistic, decrease computing time, the need for specialized equipment, etc. With new techniques come new definitions, concepts, and terms that correlate with methods that have existed for decades or even more recent ones. Parameterization, interpolation, blendshapes, motion-capture and others are concepts that often appear in the literature, in a generic way, as techniques, but which actually have different levels in information hierarchy. This paper aims to clearly classify the different techniques and concepts of the 3D facial animation literature, locating them in each step of the 3D facial animation pipeline, through a parametric analysis.